Kebijakan Pendidikan Orde Lama dan Dampaknya Terhadap Eksistensi Madrasah - M Syarif (LPPM IAI Hasanuddin Pare-Kediri, 2019)
This study focuses on the discussion on education policies issued by the Orde Lama government along with their influence on the existence of madrasas in Indonesia. Especially after the issuance of recommendations from Badan Pekerja Komite Nasional Pusat, the establishment of the Ministry of Religion along with its policies, until the publication of Republic Indonesian Law No.4 of 1950 concerning the Basics of Education and Teaching in Schools. The method used in this study is library research. The purpose of this study is to provide broader and more in-depth insight into the conditions of the madrasa in Orde Lama era. Conceptually, this era was considered as the initial milestone in the development of madrasa towards a more modern system of religious education, which combines religious subjects and general subjects in them.